Molecular characterization and identification of Vibrio cholerae variants in Malaysia / Kathryn Tham Bee Lin - Tham, Kathryn Bee Lin (2015)
Vibrio cholerae O1 El Tor variants reported to be potentially more virulent than the prototypic El Tor have emerged in Malaysia. In this study, forty-five O1 El Tor strains that were associated with cholera outbreaks and sporadic cases between 1991 and 2011 in Malaysia were studied and characterized. These clinical isolates were analyzed for the phenotypic characterization i.e., serotype, biotype and antibiogram while molecular characterization entailed detection of virulence genes and CTX prophages by Polymerase Chain Reaction (PCR), and genetic diversity by Pulsed-Field Gel Electrophoresis (PFGE). All strains were of El Tor biotype and mostly of Ogawa serotype. The strains were resistant to multiple drugs, with reduced susceptibility to tetracycline and complete resistance to erythromycin. The presence of ctxA, ctxB, ompW, rfb, rtxC, tcpA, tcpI, toxR, rstR, zot and hlyA genes were confirmed in all the strains. Analyses of the ctxB subunit showed that strains isolated in 1991 harboured El Tor cholera toxin gene (ctxB genotype 3) while sporadic strains from 2004 to 2011 had the Classical ctxB genotype 1. The 2009 cholera outbreak strains from Terengganu were of both El Tor and El Tor variants. Both the Classical and El Tor type rstR were detected in El Tor variant strains isolated between 2010 and 2011, which harboured a tandem repeat of the CTX prophage in the small chromosome, in addition to a RS1-RS1-CTX prophage array in the large chromosome. PFGE analysis showed El Tor variant strains isolated between 2010 and 2011 with the exemption of strain VC305 were highly similar to the prototypic El Tor 1991 outbreak strains with 94% similarity. Strains of El Tor variants containing the Classical cholera toxin gene are associated with cholera cases in Malaysia, however, the variant strains have not completely replaced the prototypic El Tor strains which still can be found in the country.